Unemployment, public-sector health care expenditure and HIV mortality: An analysis of 74 countries, 1981-2009 - Mahiben Maruthappu; Callum Williams; Thomas Zeltner; Rifat Atun (Edinburgh University Global Health Society, 2015)
Background: The global economic downturn has been associated with increased unemployment and reduced public-sector expenditure on health care (PSEH). We determined the association between unemployment, PSEH and HIV mortality. Methods: Data were obtained from the World Bank and the World Health Organisation (1981-2009). Multivariate regression analysis was implemented, controlling for country-specific demographics and infrastructure. Time-lag analyses and robustness-checks were performed. Findings: Data were available for 74 countries (unemployment analysis) and 75 countries (PSEH analysis), equating to 2.19 billion and 2.22 billion people, respectively, as of 2009. A 1% increase in unemployment was associated with a significant increase in HIV mortality (men: 0.1861, 95% CI: 0.0977 to 0.2744, P<0.0001, women: 0.0383, 95% CI: 0.0108 to 0.0657, P=0.0064). A 1% increase in PSEH was associated with a significant decrease in HIV mortality (men: -0.5015, 95% CI: -0.7432 to -0.2598, P=0.0001; women: -0.1562, 95% CI: -0.2404 to -0.0720, P=0.0003). Time-lag analysis showed that significant changes in HIV mortality continued for up to 5 years following variations in both unemployment and PSEH. Interpretation: Unemployment increases were associated with significant HIV mortality increases. PSEH increases were associated with reduced HIV mortality. The facilitation of access-to-care for the unemployed and policy interventions which aim to protect PSEH could contribute to improved HIV outcomes.